Jilani Kamran: An Impressionist of Nature - Asma Asghar (بازیافت)
Jilani Kamran was a renowned literary personality. As a poet and critic the valuable creative and academic asset left by him will always be remembered. He maintained his dignified and exclusive recognition as a scholar. He started his poetry in sixties and due to his specific and eclusive expression his readers were highly impressed. He  fundamentally belonged to the new poetic movement. His poetry witnessed a change in his later age and he came closer to the natural colour of poetry. That's why a marked difference can be seen in his earlier and later part of poety.